Virtual reality-based simulation of age-related visual deficiencies: Implementation and evaluation in the design process - Zavlanou, Christina; Lanitis, Andreas (My University, 2019)
Age-related changes significantly affect elderly users’ interaction with specific products and services. Nevertheless, the challenges experienced by elderly users are difficult to be perceived and understood, especially by younger people. Inspired by the concept of aging suits, we propose a Virtual Reality-based approach, where age-related visual impairments are simulated in virtual environments. The aim is to provide an approximation of the experience of viewing and interacting with a product, from the perspective of elderly persons with specific age-related visual problems. The effectiveness of the proposed approach is examined through an experiment involving package design evaluation. The experimental results demonstrate that Virtual Reality can play an important role on understanding the challenges that elderly users face, thus support the design of elderly-friendly products.
Keywords: Virtual reality; Simulation; Elderly-friendly design